El acceso efectivo a la información, participación pública y justicia en asuntos ambientales con la ratificación del acuerdo de Escazú por el Perú - Escudero Hemeryth, Andrea Stephanie (2024)
The thesis was entitled: "effective access to information, public participation and justice in environmental matters with the ratification of the Escazú Agreement by Peru." The authors' general objective was to determine how the full and effective implementation of the rights of access to environmental information, public participation in environmental decision-making processes and access to justice in environmental matters is guaranteed in Peru with the ratification of the Escazu Agreement. To meet this objective, an observational, analytical, cross-sectional and prospective study was carried out. The population was made up of OEFA officials, prosecutors and judges in environmental matters, UNAP teaching lawyers and environmental specialists from regional government line bodies. Convenience sampling was applied to this population and the survey technique. The results were that it is little and moderately true that in Iquitos there is an effective recognition and application of the rights of access to information, public participation and justice in environmental matters. Likewise, the application of the Chi Square determined that there is a relationship between the variables of the investigation. The thesis concluded that the binding nature of the Escazú Agreement guarantees the full and effective implementation of the rights of access to information, public participation in decision-making and access to justice in environmental matters.